The Effect of Hydrotherapy in Low Back Pain Patients - Walean, Monica Karina; Nyimas Fatimah (Sriwijaya Journal of Medicine, 2020)
Background: Low back pain (NPB) is the first disease that causes disabilities at all ages, and its incidence increases withage. A number of previous studies have reported that hydrotherapy has an effect on improving low back pain andincreasing flexibility.Therefore, this study aims to determine the effect of hydrotherapy on pain intensity andlumbosacral flexibility in low back pain patients at dr. Mohammad Hoesin Palembang. Methods: This study is a pre-experimental study with a one group pretest-posttest design with a sample size of 35 NPB patients. Inclusion criteriawere NPB patients who did not undergo operative action, had no contraindications to undergo hydrotherapy, andwere > 29 years old. The exclusion criteria were patients with communication disabilities and a history of low backpain due to infection, tumor and metastases. Subjects dropped out of the study if they underwent hydrotherapy lessthan three times or withdrew. Pain intensity and lumbosacral flexibility data were obtained before and after thesubject underwent hydrotherapy once a week for one month. Results: There was a decrease in pain intensity from5.57 to 4.00 (p <0.001) and an increase in lumbosacral flexibility from 48.10 to 48.73 (p = 0.014) in low back painpatients undergoing hydrotherapy. Conclusion: There is an effect of hydrotherapy on reducing pain intensity andincreasing lumbosacral flexibility in low back pain patients undergoing hydrotherapy at the Medical RehabilitationInstallation Dr. Mohammad Hoesin Palembang